Development of In Vitro Regeneration Protocol for Sweet Pepper (Capsicum annuum L.) using Cotyledon as Explant (Journal of the Bangladesh Agricultural University, 2024)
Plant tissue culture techniques offer a promising avenue for the efficient propagation of sweet pepper (Capsicum annuum L.), a valuable crop with significant agricultural importance. An effective and repeatable in vitro plant regeneration protocol was developed for the CKN-1 (Lemon yellow) and CKN-8 (Red) genotypes of sweet pepper. Utilizing cotyledonary leaf and cotyledonary node explants, various concentrations and combinations of growth regulators were tested for shoot rejuvenation. For both explants, MS medium supplemented with 8 mg/L BAP, 0.02 mg/L NAA, and 0.5 mg/L IAA was found to be most effective for achieving high rates of response and shoot induction. Notably, cotyledonary node explants outperformed cotyledonary leaf explants, displaying a remarkable 80% response within 11-12 days. Additionally, the supplementation of 1 mg/L IBA with MS medium significantly improved root initiation, with cotyledonary node explants exhibiting the highest responsiveness at 83.77%. Throughout all stages, the genotype CKN-8 (Red) consistently outperformed CKN-1 (Lemon yellow), including in the percentage of regenerated plant establishment.J Bangladesh Agril Univ 22(3): 310–316, 2024